Peripheral Nerve Regeneration through Hydrogel-Enriched Chitosan Conduits Containing Engineered Schwann Cells for Drug Delivery. Issue 1 (January 2016) - Meyer, Cora; Wrobel, Sandra; Raimondo, Stefania; Rochkind, Shimon; Heimann, Claudia; Shahar, Abraham; Ziv-Polat, Ofra; Geuna, Stefano; Grothe, Claudia; Haastert-Talini, Kirsten
Critical length nerve defects in the rat sciatic nerve model were reconstructed with chitosan nerve guides filled with Schwann cells (SCs) containing hydrogel. The transplanted SCs were naive or had been genetically modified to overexpress neurotrophic factors, thus providing a cellular neurotrophic factor delivery system. Prior to the assessment in vivo, in vitro studies evaluating the properties of engineered SCs overexpressing glial cell line-derived neurotrophic factor (GDNF) or fibroblast growth factor 2 (FGF-2 18kDa ) demonstrated their neurite outgrowth inductive bioactivity for sympathetic PC-12 cells as well as for dissociated dorsal root ganglion cell drop cultures. SCs within NVR-hydrogel, which is mainly composed of hyaluronic acid and laminin, were delivered into the lumen of chitosan hollow conduits with a 5% degree of acetylation. The viability and neurotrophic factor production by engineered SCs within NVR-Gel inside the chitosan nerve guides was further demonstrated in vitro. In vivo we studied the outcome of peripheral nerve regeneration after reconstruction of 15-mm nerve gaps with either chitosan/NVR-Gel/SCs composite nerve guides or autologous nerve grafts (ANGs). While ANGs did guarantee for functional sensory and motor regeneration in 100% of the animals, delivery of NVR-Gel into the chitosan nerve guides obviously impaired sufficient axonal outgrowth. This obstacle was overcome to a remarkable extent when the NVR-Gel was enriched with FGF-2 18kDa overexpressing SCs.